Peace, Politics, and Religion - Haynes, Jeffrey (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Relationships between peace, politics and religion are often controversial, and sometimes problematic. Religion is a core source of identity for billions of people around the world and it is hardly surprising that sometimes it becomes involved in conflicts. At the same time, we can see religion involved not only in conflict. It is also central to conflict resolution, peace-making and peacebuilding. Religious involvement is often necessary to try to end hatred and differences, frequently central to political conflicts especially, but not only, in the Global South. Evidence shows that religious leaders and faith-based organisations can play constructive roles in helping to end violence, and in some cases, build peace via early warnings of conflict, good offices once conflict has erupted, as well as advocacy, mediation and reconciliation. The chapters of this book highlight that religion can encourage both conflict and peace, through the activities of people individually and collectively imbued with religious ideas and ideals.